UPAYA MENINGKATKAN HASIL BELAJAR SEJARAH MELALUI METODE DISKUSI BAHASAN LKS SMP 4 LAMPUNG TAHUN 2009 - Yusinta Tia Rusdiana (Jurnal Artefak, 2019)
The purpose of this class action research is to find out whether the use of the discussion method in the discussion of LKS can improve the history of learning outcomes of class VIII A of SMP 4 Padang Cermin, and also to achieve student mastery learning. The formulation of the problem in this study is "Is the use of the discussion method in the discussion of LKS can improve the history of learning outcomes of students of class VII A 1st semester of SMP 1 Padang Cermin South Lampung in 2008/2009. The method used in this study is a qualitative descriptive method with classroom action research, ie researchers will conduct teaching and learning activities accompanied by partner teachers. From the results of the research that has been done, it can be concluded: The average class of historical learning outcomes of students has increased, namely before using the LKS of 68 and after using LKS of 86.1. The percentage increase in historical learning outcomes from 42 students before using LKS is 52.3% and after using LKS increased to 97% from 42 students, then in the final results of this study there was an increase of 44.6%.